Somatic Sex: On the Origin of Neoplasms With Chromosome Counts in Uneven Ploidy Ranges - Haas, Oskar A. (Frontiers in Cell and Developmental Biology, 2021)
Stable aneuploid genomes with nonrandom numerical changes in uneven ploidy ranges define distinct subsets of hematologic malignancies and solid tumors. The idea put forward herein suggests that they emerge from interactions between diploid mitotic and G0/G1 cells, which can in a single step produce all combinations of mono-, di-, tri-, tetra- and pentasomic paternal/maternal homologue configurations that define such genomes. A nanotube-mediated influx of interphase cell cytoplasm into mitotic cells would thus be responsible for the critical nondisjunction and segregation errors by physically impeding the proper formation of the cell division machinery, whereas only a complete cell fusion can simultaneously generate pentasomies, uniparental trisomies as well as biclonal hypo- and hyperdiploid cell populations. Since such somatic fusions recapitulate the fertilization process that involves a diploid oocyte and a haploid sperm, aneuploid tissues can be perceived as flawed embryonic products of somatic digynic triploidies.